Simulação do clima de 2050 em campo e seus efeitos sobre o crescimento de forrageiras - Bortolin, Livia Haik Guedes de Camargo (Universidade Federal de São Carlos, 2016)
This research was conducted to understand the climate responses of two tropical forages to a future scenario predicted for 2050, regardless of the season. We consider the hypothesis of the consortium between the two forages is a grazing alternative in a future climate. To test this hypothesis, we studied two forages under controlled atmospheric CO2 concentration and temperature in field conditions using a system named Trop-T-FACE. This system gave us the competence to mimic atmospheric conditions predicted for 2050 (600 ppm of CO2 in the atmosphere (eC) and an increase of 2 ºC in the canopy temperature). The C4 grass Panicum maximum and the C3 legume Stylosanthes capitata grew on current agricultural practice, in an area of 2500 m2 on the campus of the University of São Paulo in Ribeirão Preto – SP. We tested the hypothesis about the consortium between the two forages being a grazing alternative in a future climate. In the winter of 2013 and the autumn of 2014, the forage grew on irrigated consortium. In the autumn of 2015, S. capitata grew in monoculture without irrigation. Sixteen parcels in a ring form with 2 m of diameter were used for monitoring the growth and development of the species C3 and C4 species during growth periods of 35 days approximately after the initial cut. Several plant organization levels were accompanied under field conditions in Control plots, plots with elevated CO2 concentration (eC), under heating (eT), and under high CO2 concentration and heat (eC+eT). In the first chapter is the experiment conducted during the winter of 2013, with P. maximum in irrigated consortium with S. capitata. The climatic conditions of temperature were suboptimal for the C4 grass growth. Thus, the warming explicitly promoted the foliage development. The higher atmospheric CO2 concentration caused downregulation in leaf biomass accumulation. The changes resultant of the atmospheric alterations also caused modifications of leaf N concentration and biomass partition in the plant. Under combined treatment (eC+eT), the inhibitory effects of the CO2 increase were offset by the increment resultant of warming. Therefore, in the future climatic conditions, during the winter in the Brazilian Southeast region, the heating of the leaves will mitigate the inhibition by excess carbon, as long as the consortium is free of water and nutritional impediments. In the autumn of 2014, a new experiment was performed with P. maximum and S. capitata growing in irrigated consortium. This experiment is described in the second and third chapters. In the second chapter are the results of P. maximum in irrigated consortium. The purpose of conducting this experiment in the autumn was mainly to compare the influence of warming on the grass leaves in a warmer season. During the autumn, the treatments accelerated the leaf phenology of the C4 grass, including leaf senescence. The isolated increase in the atmospheric CO2 concentration (eC) or combined with warming (eC+eT) conditioned narrower leaves, probably by alterations in the leaf meristem formation process. Changes in leaf width may cause modifications in forage quality and affect the consumption by the cattle. However, the presence of narrower leaves was compensated by a greater number of leaves and the tiller biomass remained. On the other hand, the C3 legume growing in irrigated consortium during the autumn of 2014, presented several changes with no statistical differences in vegetative growth, despite the heat (eT) have been shown to be harmful to it. The results of this experiment are described in the third chapter. Being a legume adapted to warm climates, the main negative changes observed in S. capitata under warming (eT) were attributed to competition with P. maximum in the consortium. The separate heating (eT) stimulated further growth of the grass, which shadowed and softened the heat arrival in the C3 species. However, the warming (eT) significantly stimulated the flowering. In the treatment that simulated warming and CO2 concentration in the 2050 climate (eC+eT), there were more branches due intense flowering at the apex of the shoot and consequently interruption of apical dominance. The predicted future climate scenario is not favorable besides leaf biomass in this C3 species remaining the same among applied atmospheric regimes. Furthermore, the irrigation of extensive grazing warmed areas is economically and ecologically unviable and did not increase the availability of leaf biomass of S. capitata in the consortium in the year 2050. An experiment was conducted during the autumn of 2015, with the legume in monoculture without irrigation to identify the real influence of the irrigation on S. capitata growth. CO2 atmospheric enrichment increased neither biomass nor the leaf area. On the other hand, it occurred greater investment on flowers at the expense of vegetative shoot compartments. Nonetheless, enhancing flowering was only possible with soil water content greater than 0.3 m3 m-3. Warming combined with soil water shortage caused higher mortality of shoots. The rise in atmospheric CO2 concentration predicted for 2050 will not be enough to mitigate the damaging effects on leaf biomass production of the warming of about 2 ºC, in field conditions without irrigation, in this shrub C3 legume. Thus, the consortium, even irrigated, was not as an alternative pasture in climate predicted for 2050. The monoculture of the C3 legume without irrigation brought results even more concerning. The data obtained in these studies can base the development of new pasture management strategies. Also, they provide relevant information for the development of public policies to support the productive chain of meat and milk, the largest in Brazil and one of the largest in the world.
Keywords: Panicum maximum; Stylosanthes capitata; Mudanças climáticas; Gramínea c4; Leguminosa c3; CIENCIAS BIOLOGICAS::ECOLOGIA